From the Last Glacial Maximum to the Late Holocene: Unraveling the dynamic complexities of climate and human history in Western and Southeastern Iran - Vaezi, Alireza; Weeks, Lloyd; Routh, Joyanto (Frontiers in Earth Science, 2025)
Since the early Neolithic (∼10,000 years ago), the Iranian Plateau has witnessed the development of sedentary human settlement facilitated by periods of favorable climatic conditions prompting gradual or sweeping changes. Climate factors significantly drove the hydroclimatic conditions in western and southeastern Iran, which varied in response to the Mid-Latitude Westerlies (MLW) and Indian Summer Monsoon (ISM). In addition, the input of dust and its eastward transport from the Arabian Peninsula and North Africa coincided with the North Atlantic cooling events. Peak wet conditions during the early Holocene in southeastern (c. 11.4–9.6 ka BP) and western Iran (c. 10.2–8.6 ka BP) indicate different timings in regional precipitation. The northward displacement of the Intertropical Convergence Zone at the beginning of the early Holocene caused the ISM to expand over southeastern Iran. At the same time, it strengthened the sub-tropical high-pressure and northward expansion over western Iran, resulting in dry conditions. Between 7.8 and 6.3 ka BP, gradual weakening and southward movement of the ISM and the decrease in intensity of the subtropical high-pressure systems over the Zagros region resulted in southeastern Iran becoming mild and the western region humid. Between 6.3 and 5.0 ka BP, a decrease in solar insolation ushered dusty and arid conditions on the Iranian plateau. Notably, human activities in the region started experiencing significant changes around the mid-Holocene. A concurrence exists during the wet (c. 5.0–4.5 ka BP) and dry (c. 4.2–3.2 ka BP) periods, coinciding with the rise and decline of multiple Bronze Age settlements. These settlements flourished in exchange and trade, pyro-technologies, and agro-pastoral production, demonstrating an increasing complexity in social organization and vulnerability to climate change. After transitioning into the Iron Age, southeastern Iran experienced relatively wet conditions c. 2.9 to 2.3 ka BP and 1.6 to 1.3 ka BP coincided with major territorial expansions and advancements under the Achaemenid and Sassanian dynasties. Merging the historical and archaeological data with palaeoenvironmental conditions indicates a concurrence of unfolding climatic and cultural changes, suggesting cascading effects that led to growth or settlement decline and abandonment.